CT imaging features of COVID-19 pneumonia: initial experience from Turkey - Çinkooğlu, Akın (Diagn Interv Radiol, 2020)
PURPOSE: We aimed to demonstrate the computed tomography (CT) findings observed at the initial presentation of coronavirus disease 2019 (COVID-19) pneumonia and reveal the most frequent infiltration and distribution patterns of the disease. METHODS: A total of 185 patients (87 men, 98 women; mean age, 48.7 years), who underwent RT-PCR sampling and high-resolution CT examination at our hospital between March 15, 2020, and April 15, 2020, and got a definitive diagnosis of COVID-19 disease via initial or follow-up RT-PCR test, were included in the study. We comprehensively analyzed the most common and relatively rare CT imaging features (e.g., distribution pattern, density of the lesions, additional CT signs) in patients diagnosed with COVID-19 pneumonia. RESULTS: Thirty-eight patients (20.6%) had no evidence of pneumonia on their initial high-resolution CT images. Among 147 patients (79.4%) who had parenchymal infiltration consistent with pneumonia, 10 (6.8%) had a negative baseline RT-PCR test, and positivity was detected as a result of repeated tests. Most of the patients had multifocal (89.1%) and bilateral (86.4%) lesions. The most common location, right lower lobe, was affected in 87.8% of the patients. Lesions were distributed predominantly at peripheral (87.1%) and posterior (46.3%) areas of lung parenchyma. Most of the patients had pure ground glass opacity (GGO) (82.3%) followed by GGO with consolidation (32.7%) and crazy paving pattern (21.8%). Pure consolidation, solid nodules, halo sign, reverse halo sign, vascular enlargement, subpleural line, air-bronchogram, and bronchiectasis were the other findings observed in at least 15% of the cases. Halo sign, acinar nodules, air-bubble sign, pleural thickening and effusion, mediastinal and/or hilar lymphadenopathy were seen rarely (2%–12.9%). Pericardial effusion, pneumothorax, cavitation, and tree-in-bud pattern were not detected in our study group. CONCLUSION: Multifocal and bilateral GGO infiltration predominantly distributed in peripheral, posterior, and lower lung areas was the most common infiltration pattern.